Evaluation of University Student Eating Pattern Based on “Isi Piringku” [My Plate] Guideline and Their Correlation to Increased Body Weight during Pandemic - Dina Anandita Irawan; Zettira Dwi Zahra; Nur Jannah Binti Azhar; Sofa Rahmannia (Fakultas Kedokteran Universitas Sriwijaya, 2022)
The Ministry of Health has issued dietary guidelines, namely ”Isi Piringku” [My Plate]. However, few studies have evaluated the implementation and its relationship to nutritional status in the university student population, especially during the COVID-19 pandemic. The objectives of this study include (1) evaluating student eating patterns during the pandemic based on the ”Isi Piringku” guidelines; (2) analyze the correlation of diet to changes in body weight during the pandemic. This research was conducted using an online survey of 110 students spread throughout Indonesia in the first to eighth semesters. The analysis was carried out by descriptively comparing the median portion of the type of food to the ”Isi Piringku” recommendations and analyzing the correlation using Spearman's analysis. In 4 types of food (staple food, side dish, vegetables, and fruit), there is a gap between the median proportions eaten by respondents and recommendations including staple foods (29% and 33%), side dish (38% and 17%), vegetables (17% and 33%), and fruit (14% and 17%), respectively. However, staple food intake correlates significantly with weight gain (r=0.24, p=0.012). Conversely, protein intake mainly from vegetable products negatively correlated with weight gain (r=-0.28, p=0.030). In conclusion, there is a large gap in vegetable consumption among Indonesian students. The proportion of staple foods is considered sufficient and needs to be maintained in moderation to avoid the risk of weight gain during the pandemic.